“Ensayos preliminares para la obtención de miel a partir de yacon ( polymnia sonchifolia)y su caracterización” - Isuiza Paredes, Geiner (2004)
The present work of investigation. Conists of determining the tisioquimicas characteristics of yacón ( Polymnia Sonchifolia Qéllo variety llajun coming from Pomacocha .Amazon. As well as the stiitable parameters of precess and the characterization of the honey . The roots of yacon presented/displayed a vvater cantent : 8S:34% Ash (b.s) 2.25% Protein (b.s) 2.32% Fat (b.s) .1.77%; (b.s) 6.41% and carbohydrates (b.s) 87.24 % reducing 30.14 % saccharose 3.76 and % fructooligasacaridos sugars of 52,65%. The inmersion of yacones was determined : the fol!owing techno!ogical parameters bare must be made to the time of 5 minutes, the time of concentration of the juice of yacon was of 150 minutes unti! reaching 80º' brix . Brix the packagingto 80º C, soon the investment of the packages was made to sterili.ze the covers and cooling to the atmosphere. Reaching a performance on the basis of the raw material ot 5.20%. The honey of yacon presente/displayed a humidity 22.28% ashes 3.34% proteins 2,70% fiber 3.97%, carbohydrates 89.87% sugara reducing 18,82°/c, saccharose 9.52% and fructooligosacaridos 59.54% expreseed ( g/'l 00 g m.s.) .